2022
DOI: 10.5435/jaaos-d-21-00499
|View full text |Cite
|
Sign up to set email alerts
|

Stability in Direct Lateral vs Direct Anterior Total Hip Arthroplasty in the Context of Lumbar Spinal Fusion

Abstract: Introduction: Lumbar spinal fusion (LSF) may increase the risk of dislocation in patients who have undergone total hip arthroplasty (THA), especially when the LSF was done before the THA. Most publications evaluated patients who had undergone THA using a posterior approach to the hip, yet there are little data on the influence of other surgical approaches. The goal of this study was to evaluate the risk of THA dislocation with anterior supine-based surgical approaches to the hip in patients who have undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The surgical approach may affect the results of THA among previous SF patients. Goyal et al demonstrated that anterior supine-based approaches including direct anterior and direct lateral for THA had a low risk of instability (< 1%) from a total of 582 previous SF patients [ 38 ]. This network meta-analysis demonstrates that the subset cohort of long spinal fusion construct patients present with the greatest risk of postoperative complications following THA.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach may affect the results of THA among previous SF patients. Goyal et al demonstrated that anterior supine-based approaches including direct anterior and direct lateral for THA had a low risk of instability (< 1%) from a total of 582 previous SF patients [ 38 ]. This network meta-analysis demonstrates that the subset cohort of long spinal fusion construct patients present with the greatest risk of postoperative complications following THA.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al propose a study using the CT/X-rays matching technique of the pelvis [ 18 ]. Other authors, however, such as Goyal et al and Furuhashi et al, proposed a standing and seated radiographic study of the pelvis and spine together in AP and lateral-lateral X-rays to examine postural changes where there is likely to be the most significant risk of dislocation [ 11 , 19 ]. Behery et al and Schmidth Braekling et al propose the use of combined AP and lateral-lateral X-rays of the pelvis and spine in other positions in addition to standing and sitting, such as maximum trunk flexion position while seated or single-leg standing visualization, which emphasizes the compensatory mechanisms of patients and may provide information on patients at high risk of dislocation in THA.…”
Section: Radiological Assessmentmentioning
confidence: 99%
“…The choice of the surgical approach is a crucial factor that can significantly impact the outcomes of THA for patients with prior LA [ 18 , 19 , 20 ].…”
Section: Influence Of Surgical Approachmentioning
confidence: 99%
See 2 more Smart Citations